EXTENDING THE VISUAL CRYPTOGRAPHY ALGORITHM USING IMAGE WATERMARKING TECHNIQUE - Kotthapalli, Dilip Kumar; Anitha, Dr. V.R. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Visual cryptography is a secret information sharing technique which shares the information in the form of images. It generates noise-like random pixels on share images to hide secret information which on overlay decrypt the information. This technique is known as conventional visual secret sharing schemes. It suffers a management problem, because of which dealers cannot visually identify each share. This problem is solved by the extended visual cryptography scheme (EVCS), which adds a meaningful cover image in each share. While removing the extra cover image it produces extra noise or degrades the hidden image quality. So we propose a new image watermarking technique in this Visual Cryptography Algorithm that places a small image on the noisy image pair at the bottom right corner. So that the cover images need not be removed and it doesn’t degrade Â resolution of the secret image.